1992
DOI: 10.1002/mrd.1080320313
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule distribution during fertilization in the rabbit

Abstract: The distribution of microtubules was studied during fertilization of the rabbit oocyte by immunofluorescence microscopy after staining with an anti-alpha-tubulin antibody. In ovulated oocytes, microtubules were found exclusively in the meiotic spindle. At fertilization, the paternal centrosome generated sperm astral microtubules. During pronuclear development, the sperm aster increased in size, and microtubules extended from the male pronucleus to the egg center and towards the female pronucleus. These observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 10 publications
3
30
1
Order By: Relevance
“…The present results showed that the meiotic spindle of the porcine oocyte is peripherally located and radially oriented with its long axis as seen in other domestic species [6,8,10] and humans [16], and no rotation of the meiotic spindle occurred unlike in laboratory rodents [3,5]. Further, the meiotic spindle is barrel-shaped in the pig ( [11] and this study) and cattle [10], and is approximately 10 µm long, whereas in laboratory rodents it is much more elongated and tapered [5,23] with a length of 26.4 ± 0.3 µm in the mouse [23] and 16.4 ± 0.7 µm in the hamster (our unpublished observation).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The present results showed that the meiotic spindle of the porcine oocyte is peripherally located and radially oriented with its long axis as seen in other domestic species [6,8,10] and humans [16], and no rotation of the meiotic spindle occurred unlike in laboratory rodents [3,5]. Further, the meiotic spindle is barrel-shaped in the pig ( [11] and this study) and cattle [10], and is approximately 10 µm long, whereas in laboratory rodents it is much more elongated and tapered [5,23] with a length of 26.4 ± 0.3 µm in the mouse [23] and 16.4 ± 0.7 µm in the hamster (our unpublished observation).…”
Section: Discussionsupporting
confidence: 75%
“…Cytoskeleton organization is well known to be important for the progression of these events in mammals such as the mouse [1-4], rat [5], rabbit [6], sheep [7,8], cattle [9,10], pig [11][12][13][14][15] and human [16]. Our previous studies showed that cytoskeletal alteration is involved in the dynamic change of the cumulus-oocyte cell communication during oocyte maturation, and that the cumulus mass condition affects oocyte maturation in the pig [17,18].Observations of the early events of fertilization have indicated the paternal inheritance of a microtubule-organizing center in oocytes of rabbits [6], sheep [7], cattle [9], and pigs [12][13][14][15]19]. In pig oocytes, sperm aster enlarged during sperm decondensation and extended throughout the cytoplasm at the time of pronuclear apposition [12,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The human sperm aster formation rate at 6 h post-ICSI is 36.1% in rabbit oocyte and 60.0% in bovine oocyte (Terada et al 2000;Terada et al 2004b). The microtubule organization in these systems is derived from the paternal centrosome during fertilization, and mimics that seen in normal human fertilization Yellera-Fernandez et al 1992;Navara et al 1994). In 2004, we reported human sperm aster formation rates in rabbit oocytes after heterologous microinjection, using sperm from infertile men.…”
Section: Development Of a Functional Assay For The Human Sperm Centromentioning
confidence: 93%